ROLE OF FINE NEEDLE ASPIRATION CYTOLOGY IN SOLITARY THYROID NODULES - Singh, Dinesh Kumar; Shrivas, Ravindra Kumar; D.G., Paricharak; Nigam, Nitu; Nigam, Sanjay Kumar (Journal of evolution of medical and dental sciences, 2013)
BACKGROUND: In practical and numerical terms, the solitary nodule is the most important target of thyroid FNAC. Since FNAC can provide an unequivocal benign diagnosis in 60% of patients with benign nodules, its potential to reduce the number of unnecessary operations is significant. Of all the thyroid glands that on surgical resection prove to contain solitary nodules, 70-80% are benign adenomas and about 10-30% is malignant growth. Over the past two decades, fine needle aspiration cytology (FNAC) has become an essential step in the evaluation of thyroid nodules, due to its superior diagnostic reliability and cost effectiveness. AIMS & OBJECTIVES: The present study aims to explore the role of FNAC in the diagnosis of various thyroid lesions presenting as solitary thyroid nodules (excluding multiple nodular lesion). MATERIAL & METHODS: 140 patients of more than or equal to 15 years of age presenting with solitary thyroid nodule were the subjects of the current study. Subjects were referred for fine needle aspiration by the treating clinicians. OBSERVATIONS: Male: Female ratio was (18/122) 1:6.8 and age of the patients ranged from 15 years to 62 years. Maximum number of cases was in 3rd and 4th decades. 4 patients were in 7th decade. Cytodiagnostic break up of all 122 cases included colloid goitre 31 cases (25.5%), hyperplastic nodule 3 cases (2.5%), lymphocytic thyroiditis 2 cases (1.6%), Hashimoto's thyroiditis 7 cases (5.7%) and subacute thyroiditis 5 cases (4.0%), from non-neoplastic category. Amongst the neoplastic category, follicular neoplasm (45 cases, 36.9%) was the most common lesion and remaining included 15 cases of papillary carcinoma (12.3%), 4 cases of Hurthle cell neoplasm (3.3%), 3 cases of medullary carcinoma (2.5%), 2 cases of anaplastic carcinoma (1.6%) and a solitary case of squamous cell carcinoma (0.8%). Colloid was observed in all cases and was abundant in 18 cases (58%) and moderate in 11 cases (35.5%). Dominant cellular pattern observed in all cases and uniform follicular cells were arranged in monolayered sheets (honey comb pattern), nuclear pleomorphism was an uncommon finding, being seen in only 4 cases (13%). Foamy histiocytes or hemosiderin laden histiocytes were a fairly common finding, being observed in 23 cases (74.1%). A cytodiagnosis of follicular neoplasm accounted for 36.9% (45 out of 122) of all diagnosis rendered on adequate aspirates and 64.3% of all diagnosed neoplasms. (45 out of 70 cases), thus reflecting that this entity comprised not only the highest number of cases amongst the neoplastic group but also the most common lesion when both non-neoplastic and neoplastic lesions were considered together. Aspirates from follicular neoplasms were either moderately cellular or highly cellular. Thus good cellularity was the outstanding characteristic feature observed in all cases. Blood in the background was a consistent finding observed in almost all the cases. Scant to moderate colloid was observed in 31 cases (68.8%). The dominant pattern was one of repetitive microfollicles or acini being observed in all 45 cases (100%). Most of the cases also had cellular aggregates with nuclear overlapping. Histopathological correlation was available in 20 cases. 19 cases were consistent with cytodiagnosis although 1 case showed discrepancy. CONCLUSION: It was concluded that FNAC of thyroid is a safe, simple, cost-effective, reliable and accurate investigation for cases of solitary thyroid nodule as firm diagnosis can be made on cytology alone in vast majority of cases, thus obviating the need for unnecessary surgical procedures. Cystic lesions mandate careful clinical correlation. KEYWORDS: FNAC, Solitary Thyroid nodules, Follicular Neoplasm, Colloid Goitre, Histological Correlation.